The secure base script: Associated with early maladaptive schemas related to attachment. (17th March 2014) - McLean, Heather R.; Bailey, Heidi N.; Lumley, Margaret N.
<x xml:space="preserve">Abstract</x> Objectives To examine the relations between traditionally assessed early maladaptive schemas and the attachment‐specific secure base script (a script‐like representation of what individuals expect to happen when they face distress), to inform our understanding of beliefs about the self in relation to others. The present study took an ecologically driven approach, assessing knowledge of the secure base script from descriptions of current relationships. Design A cross‐sectional design was used. Methods One hundred forty‐six undergraduate students, recruited as part of a larger study on adversity and self‐concept, provided narrative descriptions of their current relationships. Narratives were coded for attachment‐related 'secure base' content using a secure base script scale for relationship narratives. Early maladaptive schemas were assessed with the Young Schema Questionnaire, and attachment was additionally evaluated using the Experiences in Close Relationships questionnaire. Results Self‐reported attachment avoidance and anxiety were related to secure base script content in theory‐consistent ways. The extent to which participants described secure base script content was inversely associated with four out of five maladaptive schemas characterized most centrally by disconnection from others. Furthermore, these associations remained significant when controlling for self‐reported attachment style. Self‐reported attachment avoidance and anxiety also were related to maladaptive schemas in a predictable pattern. Conclusions Results bridge cognitive and attachment theories, supporting the interrelatedness of secure base script knowledge assessed in current relationships, and schema‐related content regarding connectedness with others. Better integration of theories regarding internal representations may serve to enrich psychotherapeutic formulation from a variety of clinical perspectives. Practitioner points Schema Therapy's (Young, Klosko, & Weishaar, 2003, Schema therapy: A practitioner's guide. New York: Guilford Press) early maladaptive schemas, with themes of disconnection from others/in relationships, are related to the attachment construct of knowledge of a secure base script. Applying secure base script coding procedure to a relationship speech task provides a potentially valuable performance‐based tool for evaluating important attachment related constructs in a brief, non‐obtrusive format. Better understanding of how self‐schema and attachment constructs are associated may be of benefit to case formulation for psychotherapeutic intervention.